Kebutuhan perawatan periodontal remaja di Kabupaten Sinjai tahun 2007 - Asdar Gani; Taufiqurrahman Taufiqurrahman (Journal of Dentomaxillofacial Science, 2008)
This study was aimed to determine the periodontal treatment needs of teenagers inKabupaten Sinjai. The study samples consisted of 306 subjects, age range between15-20 years old, consisted 121 males and 185 females. Samples were selected throughstratified random sampling from two different senior high schools in Sinjai. Flatdental mirror and CPITN probes were used in this study. Periodontal condition wasevaluated using CPITN. The severity and prevalence of periodontal disease, as wellas its frequency distribution were evaluated and reported according to gender, age,frequency of dental brushing, and sample’s bad habit. In this study, only 11.8% ofsubjects demonstrated a healthy periodontal status. Bleeding was noted in 4.6% ofsubjects and calculus had the highest score (70.3%). Shallow and deep pockets werefound in 12.7% and 0.3% of the population studied, respectively. Hence, 11.8% ofsubjects didn’t need periodontal treatment. Oral hygiene instruction, throughdemonstration, instruction, etc, was needed by 33.7% of subjects. Scaling and oralhygiene instruction was needed by 77.3%. Then, 12.7% of subjects needed scalingand oral hygiene care. And 0.3% needed scaling, root planning and oral hygieneinstruction. Scaling and oral hygiene instruction is the most needed periodontaltreatment of teenagers in Sinjai.